The association between vitamin D-related gene polymorphisms and hepatitis B virus-related liver cirrhosis. Issue 4 (April 2020) - Wu, Jiali; Lin, Su; Liu, Shiying; Wan, Bo; Lin, Yehong; Wang, Mingfang; Zhu, Yueyong
Objectives: To investigate the relationship between vitamin D-related gene single nucleotide polymorphisms (SNPs) and hepatitis B-related liver cirrhosis. Methods: This study included patients with chronic hepatitis B who were admitted to the Liver Research Center of the First Affiliated Hospital of Fujian Medical University from July 2012 to August 2016. SNPs rs1544410 and rs2228570 in the vitamin D receptor gene and rs2282679 in the vitamin D-binding protein gene were detected using the imLDR™ multiple SNP typing kit. Genotype and allele frequencies were compared between groups using the chi-square test or Fisher's exact test. Results: A total of 226 patients with hepatitis B virus (HBV) infection were enrolled, including 116 with HBV-related cirrhosis and 110 patients without. The distributions of vitamin D-related gene SNPs in both groups were in accordance with the Hardy–Weinberg equilibrium. There was no significant difference in the frequency or allelic distributions of rs1544410, rs2228570, and rs2282679 between the two groups. Additionally, the SNPs were not associated with the severity of cirrhosis. Conclusion: No significant connection was identified between vitamin D-related SNPs and HBV-related liver cirrhosis.